The Strategy of Nasdem Party to Increase Women’s Political Participation in North Central Timor Regency - Yohanes Fritantus; Pionisius Minggu (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
Women’s political participation is protected by the applicable laws and regulations in Indonesia. Indonesia’s Law No. 10/2008 concerning the General Elections for Members of the People’s Representative Council, Regional Representative Council, and Regional People’s Representative Council requires political parties to fulfill 30% of the total quota for women’s representation in party management and legislative candidates in parliament. The purpose of this study was to find out the strategy taken by the Regional Leadership Council of the NasDem Party in North Central Timor in increasing political participation and its obstacles. In this study, the researchers applied the descriptive qualitative method. Results showed that women’s political participation in North Central Timor is still not fully realized. Participation that has been seen so far can be considered as “pseudo” participation because it is only to fulfill the demands of statutory regulations. This occurs because of being influenced by several factors, including a patriarchal culture that is still firmly embedded in the mindset of the people of North Central Timor, people’s mindsets that have not supported the implementation of affirmative action regulation & women’s involvement in politics, low motivation, financial factors, and lack of female figures who are interested in joining and being actively involved. For this reason, the strategy implemented by the NasDem Party identified in this study consists of 2 stages, namely planning and implementation of the strategy. Therefore, it can be concluded that women’s political participation in North Central Timor is still not fully realized and the participation that has been seen so far can be considered as “pseudo” participation because it is only to fulfill the demands of statutory regulations.